2002
DOI: 10.1111/1467-9450.00267
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal drug exposure and the conceptualization of long‐term effects

Abstract: This paper discusses several factors affecting the development of children prenatally exposed to drugs. In the "first generation" of research in this field a main factor model of disease formed the basis for a belief in the feasibility of detecting the direct pharmacological or teratogenic effects of drug exposure on long-term child development. However, the clustering of confounding variables has constituted a major problem in identifying these effects. In the last few years a "second generation" of research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…The present sample is drawn from a longitudinal project on the development of children born to mothers who used illicit drugs during pregnancy (for details see Moe and Slinning, 2002;Moe 2002;Slinning, 2004). This project initially comprised 78 substance exposed children, and 58 control children born without known biological risk to mothers with no history or evidence of alcohol or illicit drug use.…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations
“…The present sample is drawn from a longitudinal project on the development of children born to mothers who used illicit drugs during pregnancy (for details see Moe and Slinning, 2002;Moe 2002;Slinning, 2004). This project initially comprised 78 substance exposed children, and 58 control children born without known biological risk to mothers with no history or evidence of alcohol or illicit drug use.…”
Section: Samplementioning
confidence: 99%
“…As part of previous follow ups, the present sample (and the broader groups from which it is drawn) has been assessed with a number of cognitive and rating scale instruments (see Moe and Slinning 2002;Moe 2002;Slinning, 2004). Data from some of these are presented here.…”
Section: Behavioral Datamentioning
confidence: 99%
See 2 more Smart Citations
“…However, the evaluation of the effects of prenatal methadone and buprenorphine exposure is complicated by the fact that exposure to methadone or buprenorphine is only one of the factors that can influence child development. Therefore, it has been suggested that prenatal drug exposure should be studied as a risk factor within a developmental perspective (Moe & Slinning, 2002).The environment in which children are raised influences their experiences, which in turn affects brain development (Greenough, Black, & Wallace, 1987). The effects of prenatal drug exposure on children's development should therefore be evaluated in light of possible associations between exposure status and related psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%